2018
DOI: 10.1158/0008-5472.can-17-1833
|View full text |Cite
|
Sign up to set email alerts
|

GADD45β Loss Ablates Innate Immunosuppression in Cancer

Abstract: T cell exclusion from the tumour microenvironment (TME) is a major barrier to overcoming immune escape. Here we identify a myeloid-intrinsic mechanism governed by the NF-κB effector molecule GADD45β that restricts tumour-associated inflammation and T cell trafficking into tumours. In various models of solid cancers refractory to immunotherapies, including hepatocellular carcinoma (HCC) and ovarian adenocarcinoma, Gadd45b inhibition in myeloid cells restored activation of pro-inflammatory tumour-associated macr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 51 publications
(132 reference statements)
2
32
1
Order By: Relevance
“…Moreover, the IHC positive rate of GADD45B of the stage II progression group was higher than the non-progression group, but it turned out to have no significant difference in the primary tumor between stage II with liver metastasis after surgery and the simultaneous liver metastatic group. An associated study indicated that GADD45B contributed to tumor progression rather than the initiation in hepatocellular carcinoma and ovarian cancer [ 17 ]. Therefore, we infer that GADD45B may also be regarded as a potential tumor progression predictive marker in CRC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the IHC positive rate of GADD45B of the stage II progression group was higher than the non-progression group, but it turned out to have no significant difference in the primary tumor between stage II with liver metastasis after surgery and the simultaneous liver metastatic group. An associated study indicated that GADD45B contributed to tumor progression rather than the initiation in hepatocellular carcinoma and ovarian cancer [ 17 ]. Therefore, we infer that GADD45B may also be regarded as a potential tumor progression predictive marker in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, checkpoint inhibitor treatment is a major problem in tumor immunotherapy. Although immunotherapy has not been carried out in CRC widespread, it was shown that GADD45B could modulate innate immune checkpoint functions, which are amenable to therapeutic intervention to reprogram tumor-associated macrophages and ultimately overcome tumor microenvironments dependent on immunosuppression [ 17 , 21 ]. Moreover, as mentioned in the discussion above, inhibition of the GADD45B expression leads to suppression of proliferation and further prohibits tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…The dynamic crosstalk between TME and tumor cells affects cell survival and tumor progression, but it remains hard to fully understand how the autophagy fosters the cross talk between tumor and inflammatory cells. It is known that NF-κΒ is an important player during inflammatory response and tumorigenesis as well as in the polarization of tumor-associated macrophages (TAMs) 23,[87][88][89][90][91] . Recently, has been reported that autophagy has both anti-and pro-inflammatory effects in the TME by modulating NF-κΒ pathway 92 .…”
Section: Nf-κβ Autophagy and Tmementioning
confidence: 99%
“…Beyond the generic uncertainties associated with any novel drug candidate, an on-target-specific unknown in the clinical development of DTP3 relates to its potential pro-inflammatory adverse effects in patients. While producing no obvious phenotypes in unchallenged animals, genetic Gadd45b disruption was shown to enhance local inflammation and immune responses in experimental mouse models of arthritis, multiple sclerosis and oncogenesis [[29], [30], [31]]. Although in some cases, these effects appeared to be unrelated to the JNK pathway, in other cases, as in the context of arthritis, they were shown to depend on MKK7-driven JNK activation [29].…”
Section: Discussionmentioning
confidence: 99%